Adaptive Continuity in Sasak Vernacular Architecture: The Berugaq of North Lombok - Wibowo, Andi Prasetiyo; Vitasurya, Vincentia Reni; Setyonugroho, Gregorius Agung; Khaerunnisa; Pudianti, Anna; Mahendarto, Trias (RUAS, 2026)
Vernacular architectural transformation reflects the ongoing negotiation between local wisdom and modernization. This study examines material transformation in the berugaq, a traditional communal structure of the Sasak community in Bayan, North Lombok, and its implications for cultural identity. A qualitative comparative case study was conducted in two neighboring villages, Karang Bajo and East Bayan. Data were collected through field observations, photographic documentation, and semi-structured interviews and analyzed using a comparative thematic approach. The findings reveal contrasting patterns of material adaptation. Karang Bajo largely retains traditional materials, such as bamboo and thatch roofing, reflecting a strong commitment to cultural preservation and ecological harmony. In contrast, East Bayan adopts modern materials, including zinc roofing and metal connectors, driven by considerations of durability, availability, and maintenance efficiency. The findings suggest that material transformation does not necessarily result in cultural loss but can represent a process of adaptive continuity, whereby traditional forms, functions, and meanings are selectively maintained while accommodating contemporary needs. This study contributes to discussions on vernacular transformation and sustainable architecture by highlighting how local communities negotiate between heritage preservation and modernization through material practices.